The assessment, evaluation and rehabilitation of everyday memory problems. Selected papers of Barbara A. Wilson - Wilson, Barbara A., 1941- (New York : Psychology Press, Taylor & Francis Group, 2014)
'In the World Library of Psychologists series, international experts present career-long collections of what they judge to be their finest work - extracts from books, key articles, salient research findings, and their major theoretical and practical contributions.This volume of self-selected papers recognises Professor Barbara Wilson's major contribution to the study of Neuropsychology. Published over a 25 year period, the papers included here address the assessment, treatment and evaluation of rehabilitation provided to people who have memory difficulties arising from an injury or illness affecting the brain. This selection of papers includes work on errorless learning, the natural history of the development of compensatory memory systems, paging systems developed to enhance independent daily living for memory impaired people, and single case experimental designs to appraise the response of individual patients. The final section includes a practical framework for understanding compensatory behaviour, a model of cognitive rehabilitation and a discussion of the dilemmas created by the different aims of neuroscience as opposed to those of clinicians.This book will be of great interest to Clinical Psychologists, Neuropsychologists, Occupational Therapists and Speech and Language Therapists along with anyone who is interested in reducing the impact of memory problems in people who have suffered brain injury'--
'In the World Library of Psychologists series, international experts present career-long collections of what they judge to be their finest work - extracts from books, key articles, salient research findings, and their major theoretical and practical contributions. This volume of self-selected papers recognises Professor Barbara Wilson's major contribution to the study of Neuropsychology. Published over a 25 year period, the papers included here address the assessment, treatment and evaluation of rehabilitation provided to people who have memory difficulties arising from an injury or illness affecting the brain. This selection of papers includes work on errorless learning, the natural history of the development of compensatory memory systems, paging systems developed to enhance independent daily living for memory impaired people, and single case experimental designs to appraise the response of individual patients. The final section includes a practical framework for understanding compensatory behaviour, a model of cognitive rehabilitation and a discussion of the dilemmas created by the different aims of neuroscience as opposed to those of clinicians. This book will be of great interest to Clinical Psychologists, Neuropsychologists, Occupational Therapists and Speech and Language Therapists along with anyone who is interested in reducing the impact of memory problems in people who have suffered brain injury'--
Includes bibliographical references and index.
Keywords: Memory; Memory disorders -- Treatment